The Management of School Operational Assistance (BOS) at the Vocational High School Level in Tulin Onsoi Subdistrict, Nunukan District - Umra Iwa Davi; Cepi Safruddin Abdul Jabar (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to analyze the management of School Operational Assistance (BOS) funds in vocational high schools in Tulin Onsoi Subdistrict, Nunukan Regency, North Kalimantan, focusing on budgeting, accounting, auditing, and accountability. Using a qualitative method with a phenomenological approach, the research involved principals, treasurers, teachers, school committees, and parents from three schools: SMKN 1 Tulin Onsoi, SMKN 1 Sei Menggaris, and SMKN 1 Sembakung Atulai. Data collection was conducted through interviews and document studies, and the data were analyzed using an interactive model comprising data collection, condensation, presentation, and conclusion. The results indicate that budgeting involves participatory preparation of RKAS at the start of the academic year, guided by school programs and inputted into the ARKAS application. Although treasurers demonstrate good performance, their educational background is not aligned with financial management fields. Accounting practices ensure timely BOS disbursement and compliance with regulations. Auditing is carried out monthly, and evaluations are conducted at the end of each stage. Accountability is maintained through transparent reporting to internal and external stakeholders. Overall, the management of BOS funds adheres to technical guidelines, with no reported dissatisfaction among stakeholders.